056 Efficacy and safety of the Bruton's tyrosine kinase inhibitor evobrutinib (M2951) in patients with relapsing multiple sclerosis over 48 weeks: a randomized, placebo-controlled, phase 2 study. (29th July 2019) - Montalban, Xavier; Arnold, Douglas L; Weber, Martin S; Staikov, Ivan; Piasecka-Stryczynska, Karolina; Gillett, Alan; Martin, Emily C; Syed, Sana; Dangond, Fernando; Wolinsky, Jerry S
Abstract : Introduction: Evobrutinib (M2951) is a highly specific oral inhibitor of Bruton's tyrosine kinase, a key regulator of B cell and macrophage functions implicated in MS. Methods: In this double-blind, phase 2 study (NCT02975349 ), adult patients (≤65 years) with relapsing MS (RMS) were randomized to evobrutinib 25 mgQD, 75 mgQD, 75 mgBID, placebo, or open-label dimethyl fumarate (240 mgBID; reference arm) for 48 weeks; placebo-treated patients switched to evobrutinib 25 mgQD after 24 weeks. The primary endpoint was the total number of T1 gadolinium-enhancing (T1Gd+) lesions at Weeks 12, 16, 20, and 24. Secondary endpoints included annualized relapse rate (ARR), MRI measures at Weeks 24 and 48, and safety. Results: Among 261 patients, the sum of T1Gd+ lesions over Weeks 12–24 was reduced with evobrutinib 75 mgQD (p=0.002) and 75 mgBID (p=0.03); a dose response was observed (p=0.001). There was no evidence of change in effect on T1Gd+ lesions (mean±SD; Wilcoxon signed-rank test) between Weeks 24 and 48 with evobrutinib 75 mgQD (0.28±0.91 to 0.85±2.87; p=0.57) or 75 mgBID (0.24±0.88 to 0.49±1.22; p=0.23). ARR (unadjusted [95%CI]) was 0.25 (0.12–0.44) for evobrutinib 75 mgQD and 0.11 (0.04–0.25) for 75 mgBID over 48 weeks, and 0.37 (0.17–0.70) for placebo over 24 weeks. Evobrutinib appeared well-tolerated. Shifts to Grade 3–4 ALT and AST elevations from normal (grade 0) occurred in 8 (5.4%) and 6 (3.9%) evobrutinib-treated patients respectively, driven by events with onset within the first 24 weeks. Conclusions: Evobrutinib is the first BTK inhibitor to demonstrate disease activity reduction in RMS. The observed benefit-risk profile supports further clinical development.